Psychometric properties of the polish version of the Dysfunctional Thoughts about Caregiving Questionnaire (DTCQ) - Katarzyna Sanna; Maciej Kościelniak; Jarosław M. Michałowski; Andrés Losada-Baltar; Konrad Piotrowski (PLoS ONE, 2025)
Dysfunctional thoughts about caregiving are defined as rigid and inappropriate interpretations of one’s experiences, behaviors, thoughts, or feelings that are associated with providing care to a dependent relative. The present study examined the psychometric properties of the Polish adaptation of the Dysfunctional Thoughts about Caregiving Questionnaire (DTCQ). DTCQ was administered to 618 family caregivers of people with chronic health problems. As the Confirmatory factor analysis supported both one and two-factor structure of the DTCQ, following the principle of parsimony, one-factor model was considered more appropriate. Construct validity was also supported by significant and theoretically expected relationships between DTCQ and depression, identity formation or sociodemographic variables. In conclusion, this study is the first to provide preliminary evidence for the reliability and validity of the DTCQ as a measure of dysfunctional thoughts in Polish family caregivers.